Produksi dan Kualitas Susu Sapi FH Laktasi yang Diberi Pakan Daun Pelepah Sawit - Riski, P.; Purwanto, B. P.; Atabany, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
This study was done to determine milk production and its quality of FH cows fed oil palm frond (OPF) for 3 months in UPT of Livestock Breeding Station Kampar Riau. 4 x 4 Latin Square design was used in the present study using 4 lactating FH cows and 4 combination of elephant grass and OPF as feeding treatments. The animals were kept in individual stanchion and fed with waste of tofu as concentrate (40% dry matter base) and roughage (60% dry matter base). The feeding treatments were 100% EG, 75% EG + 25% OPF, 50% EG + 50% OPF and 25% EG + 75% OPF. Parameters Measured were feed consumption, milk production and milk quality (density, total solid, fat, solid non-fat and protein). The results showed that feeding of OPF signiicantly inluenced (P<0.01) in dry matter and crude protein intakes. Feeding OPF by 75% signiicantly decreased (P<0.01) milk production. However, there was no effect of any OPF consumption level on milk quality. In was concluded that feeding OPF as feed source of roughage for lactating cow up to 50% of the total roughage able to maintain milk production and its quality.